Dangua Fang induces anti-glucolipid metabolism disorder effects similar to those of direct NFIL3 inhibition - Han, Zhuang; Jin, Linxi; Wang, Zhita; Yang, Liuqing; Li, Liang; Ruan, Yi; Chen, Qiwei; Yao, Shuhong; He, Weidong; Heng, Xianpei (Frontiers in Microbiology, 2025)
BackgroundDangua Fang (DGF) is a traditional Chinese herbal formula widely used to regulate glucolipid metabolism. Nuclear factor, interleukin-3 regulated (NFIL3) plays a regulatory role in intestinal fat absorption and energy metabolism. Gut microbiota can modulate NFIL3 expression and affect host metabolism.PurposeThis study aimed to investigate the effects of DGF or NFIL3 inhibition on the gut microbiota and their metabolites in mice with glucolipid metabolism disorder (GLMD) and explore the relationship between DGF anti-GLMD effects and those of direct NFIL3 inhibition.MethodsA GLMD mouse model was established by induction with a high-glucose and high-fat diet. The mice were divided into the control group (CG), model group (MG), DGF group (DFG), DGF + siRNA group (DFSG), and siRNA group (SG). The mice were administered sterile water, DGF, and/or intraperitoneal injections of siRNA-NFIL3 or normal saline for 15 weeks, following which glucolipid metabolic indicators, NFIL3 levels, and histopathological alterations in the liver and small intestinal tissues were evaluated. Additionally, the gut microbiota and differential metabolites were analysed, and linear regression analysis was conducted between gut microbial species and metabolic indicators to assess the role of the gut microbiota in metabolic regulation.ResultsSignificant differences were observed between the CG and MG groups for various indicators. Compared with that in the MG group, the GLMD in the DFG, DFSG, and SG groups was significantly improved, and the pathological morphology of the liver and small intestine was altered. The NFIL3 mRNA and protein expression levels in the serum, liver, and small intestine were significantly decreased. The relative abundance of Bacteroidota decreased, whereas that of Firmicutes increased, and changes in the gut microbiota significantly correlated with serum total cholesterol (TC), triglyceride (TG), and free fatty acid (FFA) levels. Moreover, lipid metabolism-related pathways were significantly altered in all three intervention groups.ConclusionDGF reduced NFIL3 expression in GLMD mice, regulated the gut microbiota and their metabolites, and altered lipid metabolism-related pathways, with anti-GLMD effects similar to those of direct NFIL3 inhibition.